Chronic urticaria: a clinico-etiological study and autologous serum skin test role in chronic idiopathic urticaria - Badabagni, Purnachandra; Thammineedi, Sruthi; Birudala, Ramadevi (International Journal of Research in Dermatology, 2021)
Background: Appearance of wheals daily for more than six weeks is chronic urticarial (CU). No cause is identified in about 50-70% of chronic urticaria patients and are labelled as chronic idiopathic urticaria (CIU). The aim of the present study is to study the clinical and etiological pattern of chronic urticaria and to find out the incidence of autoimmune urticaria by performing autologous serum skin test (ASST) in patients with CIU. Methods: This was a cross sectional study enrolling 100 chronic urticaria patients satisfying including and excluding criteria. The study was done for a period of 1 year. ASST was done in all the CIU patients after recording detailed history, complete physical and systemic examination. Results: Most of the patients (33%) were in 21-30 years age group with female preponderance (66%). Students (38%) followed by house wives (27%) were majorly involved. 21% patients had history of atopy and 8% had abnormal thyroid function tests. Causative factors noticed in 46% patients and remaining were idiopathic (54%). Infections (32.6%) constituted the major etiological factor followed by physical urticaria (30.4%), food (23.9%), medication (11%) and inhalants (2.1%). In infective agents, 46.6% were bacterial followed by helminthic (33.3%). In 29.6% of CIU patients, the ASST was positive indicating auto-immune urticaria. Conclusions: The etiology cannot be identified in most number of patients and hence they were labelled as CIU and the common causative agents observed were infections followed by physical urticaria, food and medication. ASST is considered as the relevant screening test to detect autoimmune urticaria.